Increasing Senior High School Students’ Mathematical Problem-Solving Ability and Mathematical Disposition Through Problem-Based Learning Assisted by Simple Mathematics Kit - Achmad Mudrikah (STAI Hubbulwathan Duri, 2022)
This research intends to reveal the increasing senior high school students' mathematics problem solving ability and their mathematical disposition. The study involved 124 private secondary school students consisting of two types of school, namely ordinary private schools and private schools managed by Islamic boarding schools. In addition to examining mathematical problem-solving ability and mathematical dispositions of students based on the type of school and type of learning, this research is also researched based on the students' prior mathematical abilities. This experimental study involved 124 students as the research sample. To obtain the data, pre-test and post-test were conducted. Meanwhile, to analyze the data, the researcher implemented two-way ANOVA. The results showed that the mathematical problem-solving ability and mathematical dispositions of students who used problem-based learning assisted by simple mathematics kit was better than students who only received problem-based learning. Students from Islamic boarding schools can show better problem-solving ability when studying mathematics with problem-based learning assisted by simple math kits. Students from Islamic boarding private school gain better problem-solving ability than students from non-boarding private school, especially students who have high and medium prior mathematical abilities.